Overview of the results of the Rapid Molecular Test Examination on Pulmonary Tuberculosis Suspect Patients at RSUD Ulin Banjarmasin in 2023 - Elizabeth Chabaria; Wulan Pratiwi; Rizki Perdani (UPPM Politeknik Unggulan Kalimantan, 2024)
Tuberculosis is a chronic infectious disease caused by bacteria Mycobacterium tuberculosis which usually live in parts of organs that have a high oxygen content, namely the lungs and other organs. This study aims to determine the description of the results of rapid molecular test examinations in patients with suspected pulmonary tuberculosis at the Ulin Hospital, Banjarmasin in 2023, using a quantitative descriptive design cross sectional based on secondary data from rapid molecular test examination results. The research method used a total sampling of 1,782 samples. The results of the study were 0.50% rifampicin resistant, 14.40% rifampicin sensitive, 1.00% rifampicin indeterminate and 84.10% negative, 16.83% early elderly age category and 60.33% male gender. The conclusion of the research results was that the highest percentage of negative examinations was due to the government program for every person who had contact with TB sufferers who was directed to carry out direct examinations using rapid molecular test, in the early elderly age category due to a decrease in the ability to reactivate previously acquired immunity and additional factors as well as in male gender which is caused by several factors such as smoking, drinking alcohol and lack of knowledge about the disease. Keywords : Mycobacterium tuberculosis, Rapid Molecular Test, Rifampicin